Effectiveness of a dehumidifying render system in tackling rising damp: Laboratory, small scale and field tests. (1st November 2021) - Sardella, Alessandro; Lubelli, Barbara; Bonazza, Alessandra
Highlights: The behaviour of a two-layer "dehumidification" render system has been elucidated. A multiscale approach, including lab, scale models and field test, has been used. The render system can transport moisture and salts to the surface. The render system does not lead to a reduction of the moisture content in the wall. The durability of the render system decreases significantly in the presence of high salt content. Abstract: In this research, a commercial 2-layers render system, proposed by the producer for the de-humidification of walls affected by rising damp and salts, has been studied. The research aimed at understanding the moisture and salt transport behaviour of the render system, assessing its ability to favour drying of the wall in comparison to traditional renders, and evaluating it durability in the presence of moisture and salts. Both layers of the render have been characterized in laboratory: composition porosity, pore size distribution, water absorption by capillary and drying behaviour have been measured. The performance of the render system in the presence of moisture and salts has been experimentally evaluated in small scale models and in a field test; this has been done by assessing the moisture and salt content in the render and in the masonry substrate, at different times after the application of the render. Both layers were found to easily transport water and salts, thanks to their high porosity. In the small scale models, the accumulation of salts in the render resulted into efflorescence and moisture spots at the surface due to the hygroscopic behaviour of the salt. No reduction of the moisture content in the walls affected by rising damp was measured after the application of the render. When applied in the field test, the render system did not result in a reduction of the moisture content in the wall in comparison to the previously existing cement-based render.